Synthesis of Multiwalled Carbon Nanotubes on Different Cobalt Nanoparticle-Based Substrates - Nicolas Moreau; Antonio Fonseca; Danilo Vuono; Joseph Delhalle; Zineb Mekhalif; Pierantonio De Luca; Janos B.Nagy (Inorganics)
The primary aim of this research was to identify the optimal experimental conditions for obtaining aligned carbon nanotubes, temporarily leaving aside aspects such as the purity of carbon nanotubes, which is nonetheless crucial for potential applications in the field of nanoelectronics. The predefined alignment of CNTs can significantly influence the performance and efficiency of electronic components. In this study, two different catalytic supports based on cobalt nanoparticles, Co/SiO2/Si and Co/C, have been utilized and compared in the catalytic chemical vapor deposition (CCVD) synthesis of CNTs. Various parameters have been examined, including the nature and thickness of the catalyst, the reaction temperature, and the pressure of the acetylene mixture entering the reactor. The results indicate that the optimal temperature for the Co/SiO2/Si catalyst is 800 °C, while for the Co/C catalyst, it is 450 °C. The optimal Co layer thickness should be between 20 and 30 Å. CNT growth occurs from the top in the Co/C system, whereas bottom-up growth is characteristic of the Co/SiO2/Si catalyst, making the latter more suitable for the synthesis of CNTs intended for nanoelectronic devices.